Subject, society and culture - Boyne, Roy (Theory, culture & society, 2001)
"Roy Boyne explores the relationships between visual culture, social theory and the individual and argues that the sociological removal of the individual subject must be challenged. However, so too must humanist accounts which emphasize only struggles for freedom and the longing to create. Individual subjects are simultaneously engaged and disengaged. The narration of their actions and contexts from both social and existential standpoints is crucial for beginning to understand the human condition." "The positive critique of the two most important currents in sociological thought today, Bourdieu's field theory and Latour's actor network theory, is supplemented by examinations of the presentation of the subject in both art and film. The argument of the book, developed through case studies of Barnett Newman, Georg Baselitz, Francis Bacon, Krzysztof Kieslowski and David Cronenberg, is that the highest aspirations of both social science and the humanities are served by keeping together the social and existential moments of the individual subject." "This book will be essential reading for everyone interested in social theory, contemporary art and film studies. It will also be a key reference point for debates between sociology and cultural studies."--BOOK JACKET.